1982
DOI: 10.1111/j.1469-8137.1982.tb03304.x
|View full text |Cite
|
Sign up to set email alerts
|

DEVELOPMENT OF EXTERNAL HYPHAE BY DIFFERENT ISOLATES OF MYCORRHIZAL GLOMUS SPP. IN RELATION TO ROOT COLONIZATION AND GROWTH OF TROYER CITRANGE

Abstract: SUMMARYThe hypothesis was tested that the amount of external hyphae of a vesicular-arbuscular mycorrhizal (VAM) fungus extending from roots out into soil is not always proportional to the extent of colonization of the root cortex. Growth enhancement and amount of external hyphae were compared for eight isolates of five Glomus spp. that differed in their geographic origin and capacity to enhance growth of Troyer citrange, but were similar in their capacity to extensively colonize Troyer citrange roots. In gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
3
13

Year Published

1990
1990
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(78 citation statements)
references
References 11 publications
1
61
3
13
Order By: Relevance
“…Neste trabalho, esse efeito inibidor não foi observado para G. clarum e G. etunicatum, que apresentaram praticamente a mesma porcentagem de colonização radicular nos dois substratos (Quadro 1). Nesse caso, a colonização micorrízica deve ter sido controlada por fatores genéticos que podem ser originários da planta e/ou do isolado de fungo empregado (GRAHAM et al, 1982).…”
Section: Resultsunclassified
“…Neste trabalho, esse efeito inibidor não foi observado para G. clarum e G. etunicatum, que apresentaram praticamente a mesma porcentagem de colonização radicular nos dois substratos (Quadro 1). Nesse caso, a colonização micorrízica deve ter sido controlada por fatores genéticos que podem ser originários da planta e/ou do isolado de fungo empregado (GRAHAM et al, 1982).…”
Section: Resultsunclassified
“…A espécie de FMA com maior percentagem de colonização foi G. margarita, cerca de 8 %, diferindo significativamente das demais (P < 0,01), que, por sua vez não diferiram entre si e apresentaram colonização média de 4,5 %. Verificase que nem sempre existe relação direta entre a percentagem de colonização radicular e a eficiência micorrízica (Graham et al, 1982), conforme foi demonstrado para a produção de biomassa (Figura 1a e 1c) Com relação ao conteúdo, não houve efeito da micorrização. O P geralmente tem seu teor aumentado nas plantas micorrizadas, mas esse efeito não foi constatado nesse experimento.…”
Section: Resultados E Discussão Experimento 1 Absorção E Translocaçãunclassified
“…Sanders & Tinker (1973) found that this may lead to an increase of the inflow of phosphorus to the roots which was subsequently found to be proportional to the amount of external mycelium (Sanders et al 1977). Taking the matter further, Graham, Linderman & Menge (1982) suggested that lack of growth enhancement could reflect limited production of external hyphae rather than limited root colonization.…”
Section: Infection Of Roots By Vam Fungimentioning
confidence: 99%
“…The correlation between the length of active external hyphae and root colonization was significant whereas that between the length of total external hyphae and root colonization was not. Graham, Linderman & Menge (1982) found that internal root colonization could exceed 95% without a proportional development of external mycelium and attributed this to restrictive soil factors.…”
Section: Infection Of Roots By Vam Fungimentioning
confidence: 99%
See 1 more Smart Citation